The heated-induced gelation of soy protein isolate at subunit level: Exploring the impacts of α and α′ subunits on SPI gelation based on natural hybrid breeding varieties. (January 2023) - Fu, Hongling; Li, Jiaxin; Yang, Xiaoqing; Swallah, Mohammed Sharif; Gong, Hao; Ji, Lei; Meng, Xiangze; Lyu, Bo; Yu, Hansong
Abstract: Soy protein isolate (SPI) is widely used in the food industry as a gelling agent due to its high water-holding capacity and gelation. As a key in elucidating the structure-function relationships of SPI, subunit composition can explain many functional properties of soy protein. In this study, to explore the influence of α and α′ subunits on the gel properties of soy protein, the gel strength and water holding capacity of the heat-induced gel with missing subunits were determined. Texture Profile Analysis (TPA) showed that gel strength from large to small was α′-lack > (α and α′)-lack > native > α-lack, and the lack of α′ subunit significantly enhanced ( p < 0.05) the gel strength and water-holding capacity of the resultant gels. In the gel formation process, microstructure observation of the gels revealed that the α′-lacking gel had a more uniform and denser network structure with higher storage modulus, promoting more water molecules to be bound in the gel structure as immobilized water and exhibiting higher thermal stability. Subsequently, the lack of α′ subunit increased the zeta potential, surface hydrophobicity (H0 ), and fluorescence intensity of the gel. The deletion of the α′ subunit promoted the exposure of hydrophobic groups with more hydrophobic amino acids and promoted the aggregation of the subunits after heat treatment. These changes in the physicochemical properties of the gel affected their heat-induced gelation. In addition, gel solubility results signify that hydrophobic and disulfide bond interactions are the main forces in the gel formation process. Thus, the deletion of the α′ subunit will facilitate the development and application of soy protein products in food processing and improve their gel properties. This study will benefit the application of soy protein at the subunit level in traditional dairy products based on heated-induced gelation. Graphical abstract: Image 1 Highlights: Soy proteins with α or α′ subunit deficiency showed different gelling properties. The α′-lack significantly improved the gel strength, water holding capacity. Gel network prepared from α′-lacking SPI had the densest structure. α′ subunit-deficient soy protein might be a good candidate for gel production in the food industry.